Top 3 differentials in pediatric radiology a case review - Stein-Wexler, Rebecca (Top 3 differentials., 2019)
The highest-yield, most complete pediatric radiology exam preparation and learning tool available today Top 3 Differentials in Pediatric Radiologyby renowned pediatric radiologist Rebecca Stein-Wexler and colleagues is part of a series of radiology case books that mirror the highly acclaimed O'Brien classic, Top 3 Differentials in Radiology. Each case is formatted as a two-page unit. The left page features clinical images, succinctly captioned findings, and pertinent clinical history. The right page includes the key imaging gamut, differential diagnoses rank-ordered by the ""Top 3,"" additional.